The Relationship of the Role of Parents and Information Media with HIV/AIDS Prevention Behavior in Adolescents at SMAN 75 Jakarta - Yenti Herawati; Ritanti (Nursing and Health Sciences Journal (NHSJ), 2021)
HIV is a virus that attacks the human immune system and if the condition gets worse and results in various complications, the disease will cause AIDS or Aquired Immune Deficiency Syndrome. Adolescent behavior at this time tends to be at risk with promiscuity everywhere so as to increase the incidence of HIV/AIDS for adolescents. The purpose of the research actually for determine the relationship between the role of parents and information media with HIV/AIDS prevention behavior for adolescents at SMAN 75 Jakarta. The type of research is quantitative with cross sectional research design and analyzed by Chi-Square Test. This research conducted in March to June 2020 at SMAN 75 Jakarta involving as of 154 respondents, and the sampling using a random sampling technique. The statistical test results using Chi-Square stated that a significant relationship between the role of parents and information media. (p = 0.007). On the information media with HIV / Aids prevention behavior showed a significant relationship (p = 0,000). It is recommended to students, schools and parents to work together in efforts for prevention of HIV/AIDS.